2022
DOI: 10.3389/fphys.2022.998380
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effects of physical inactivity on peripheral and brain vasculature in humans: Insights into mechanisms, long-term health consequences and protective strategies

Abstract: The growing prevalence of physical inactivity in the population highlights the urgent need for a more comprehensive understanding of how sedentary behaviour affects health, the mechanisms involved and what strategies are effective in counteracting its negative effects. Physical inactivity is an independent risk factor for different pathologies including atherosclerosis, hypertension and cardiovascular disease. It is known to progressively lead to reduced life expectancy and quality of life, and it is the fourt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 388 publications
0
3
0
Order By: Relevance
“…Numerous studies have demonstrated that regular physical activity and exercise can significantly reduce the risk of cardiovascular disease, metabolic syndrome, and type 2 diabetes while also benefiting bone mineral density, muscle mass, and mood [49]. Even relatively short periods (less than four weeks) of bed rest without physical activity lead to negative structural and functional changes in various organs [50].…”
Section: Mirnas In Physical Activity and Exercisementioning
confidence: 99%
“…Numerous studies have demonstrated that regular physical activity and exercise can significantly reduce the risk of cardiovascular disease, metabolic syndrome, and type 2 diabetes while also benefiting bone mineral density, muscle mass, and mood [49]. Even relatively short periods (less than four weeks) of bed rest without physical activity lead to negative structural and functional changes in various organs [50].…”
Section: Mirnas In Physical Activity and Exercisementioning
confidence: 99%
“…The mechanisms by which physical activity/aerobic exercise improve aspects of brain health/cognitive function are less clear; however, evidence points towards the fact that increased physical activity [ 110 ] and other forms exercise training (e.g., high-resistance inspiratory muscle strength training) [ 111 ] promote increased cerebrovascular function in ML/O adults. These precise mechanisms are under investigation, but evidence shows that exercise increases circulating levels of the myokine Irisin, which is associated with improved cognitive function [ 112 , 113 ].…”
Section: Lifestyle and Select Pharmacological Strategies For Targetin...mentioning
confidence: 99%
“…This prevalent lifestyle pattern not only impairs immune function but is also intricately linked to various chronic disease risk factors, such as hypertension. Sedentary behavior contributes to endothelial dysfunction, 7,8 insulin resistance, 9,10 altered lipid metabolism, 11 and, critically, amplified low‐grade inflammation, as evidenced by elevated levels of cytokines like IL‐1, IL‐6, and TNF‐α 12,13 . These factors cumulatively heighten the risk of developing hypertension.…”
Section: Introductionmentioning
confidence: 99%